Fisheries Exploitation in the Indian Ocean : Threats and Opportunities - Rumley, Dennis (Book collections on Project MUSE., 2009)
The book aims to further the debate on the impacts of fisheries policies in the Indian Ocean Region in order to facilitate a new regional policy direction. A key argument of the volume is that ecologically sustainable and socially just development and management of Indian Ocean fisheries require a paradigm shift in the perceptions and policies of major stakeholders. A central policy challenge is to identify a collective regional interest for fisheries and accordingly the development of integr ...